Knowledge of Basic Life Support among Dental Surgeons: A Web-Based Cross-Sectional Study - Keshwar, Shashi; Shankar, Daya; Sarraf, Deependra Prasad; Grover, Sonal; Gupta, Pramendra Prasad (Journal of Drug Delivery and Therapeutics, 2020)
Introduction: Basic life support (BLS) refers to preserving an airway and promoting breathing and circulation without the use of any tools. It saves lives if given timely. The lack of training and knowledge of BLS might lead to tragic consequences.Objective: To assess the knowledge regarding BLS among dental surgeons.Methods: A web-based cross-sectional study was conducted among dentists in Haryana, during April-May 2020 using a semi-structured proforma. It consisted of sociodemographic data and 11 close-ended items on BLS. Score 1 was given for each correct answer. A google form was prepared via docs.google.com/forms and the link was sent to the participants via social media platforms like WhatsApp and Viber. The filled questionnaires were extracted from the Google Forms and exported to Microsoft Excel 2016. Descriptive statistics like mean, frequency and percentage were calculated to present the study findings using Statistical Package for the Social Sciences (SPSS) software (version 21).Results: Out of 73 participants, 59 (80.8%) were male and 60 (82.2%) belonged to age group of 31-45 years. Forty one (56.2%) participants had completed a bachelor of dental surgery. Mean (±SD) knowledge score was 8.75±2.46. Thirty eight (52.1%) participants scored less than 50% of the maximum score. The knowledge score was high in male and aged 31-45 years and it was statistically significant (P-value